Endophytic fungus Bipolaris sp. CSL-1 induces salt tolerance in Glycine max.L via modulating its endogenous hormones, antioxidative system and gene expression. Issue 1 (31st December 2022) - Lubna,; Khan, Muhammad Aaqil; Asaf, Sajjad; Jan, Rahmatullah; Waqas, Muhammad; Kim, Kyung-Min; Lee, In-Jung
ABSTRACT: Salinity stress is one of the most serious environmental stress that inhibits plant growth. In this study, we adopted an environment friendly technique and screened different plant growth-promoting fungi for different plant growth promoting (PGP) traits and salinity stress. Among those isolates, Bipolaris sp. CSL-1 was selected based on plant growth-promoting characteristics, such as producing indole-3-acetic acid (IAA), gibberellins (GAs), organic acids and resistance to sodium chloride (NaCl) stress. Here, we found that inoculating soybean with isolate CSL-1 significantly increased shoot and root length, shoot and root fresh and dry weight and chlorophyll content under NaCl stress (200 mM). Endogenous abscisic acid (ABA) levels were significantly decreased, whereas salicylic acid (SA) levels were increased in CSL-1-inoculated plants under NaCl stress. NaCl-treated noninoculated plants showed higher levels of antioxidants and oxidative stress such as peroxidase, polyphenol oxidase (PPO), malondialdehyde (MDA) and superoxide anion (SOA). Furthermore, CSL-1 inoculation improved soybean resistance to NaCl stress, and there was a significant decrease in GmFDL19, GmNARK, and GmSIN1 expression levels. As a result, the fungal isolate CSL-1 mitigates the effect of salt stress and enhance soybean growth and might be used as a valuable ecofriendly microorganism resource in salt-affected areas.